Egoizm Maksa Stirnera a filozoficzne korzenie coachingu = Max Stirner`s Egoism and the Philosophical Roots of Coaching - Uglik, Jacek (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In the article, I delve into the challenges surrounding the definition of coaching and aim to identify its philosophical roots, including the ideas of Max Stirner, a 19th-century German thinker. Coaching inherently entails an impetus to maximize personal potential, which aligns with Stirner`s proposition that prioritizes the realization of one`s own needs over those of others, thereby making oneself the paramount focus in the interaction with the world. It appears that among the various branches of coaching, Stirner`s ideas resonate most strongly with a variant that specifically emphasizes the holistic development of individual potential. Stirner`s concept caters to the individual and centers around providing support, which I tentatively refer to as the "self-centered approach".
Keywords: Stirner, Max (filozof niemiecki; 1956- ); egoizm; coaching; filozofia; jedyny; jednostka; swojość; egoism; philosophy; the Ego; individual; ownness